Minimally invasive diagnosis of sarcoidosis by EBUS when conventional diagnosis fail - Eckardt, J.; Olsen, K.E.; Jørgensen, O.D. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2010)
Background: Endobronchial ultrasound-guided transbronchial fine-needle aspiration (EBUS) is a minimally invasive method used routinely for mediastinal staging of patients with lung cancer. EBUS has also proved to be a valuable diagnostic tool for patients with different intrathoracic lesions who remain undiagnosed despite bronchoscopy and CT-guided fine-needle aspiration. Objective: The present study focused on EBUS for diagnosing sarcoidosis. Design: During a 3-year period 308 of 601 patients who underwent EBUS at our institution were referred for further diagnostic of a radiologically suspicious lesion in the lung parenchyma (n=195), enlarged lymph nodes in the mediastinum (n=89), a suspicious tumor in the mediastinum or pleural disease (n=24) but no one had a definite histological diagnosis. All charts were reviewed retrospectively. Results: Of the 308 patients 43 (14%) were eventually diagnosed with sarcoidosis. Thirty-three (77%) were diagnosed with EBUS. In the remaining 10 patients EBUS did not provide adequate tissue samples in 4 (9%) and in 6 patients (14%) EBUS provided adequate tissue but no definite diagnosis. EBUS was significantly better to establish the diagnosis in patients with enlarged mediastinal lymph nodes compared with isolated lung parenchymal involvement (85% vs 63%, p< 0.05). Conclusion: EBUS is a valuable minimally invasive diagnostic modality to establish the diagnosis of sarcoidosis of unselected patients with undiagnosed intrathoracic lesions after conventional work up – particularly if patients have enlarged mediastinal lymph nodes. This minimally invasive procedure provides a final diagnosis without exposing the patient to the risk of complications from more invasive procedures.